DIAGRAM FILOGENIK HASIL SEKUENS BASA DNA MENGGUNAKAN PROGRAM MEGA-7 (MOLECULAR EVOLUTIONARY GENETICS ANALYSIS) - Harumi Yuniarti; Bambang Cholis S; Astri Rinanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2016)
Sequencing techniques Deoxyribonucleic Acid (DNA) at this time is a method to identify the genetic basis of living beings, including to determine the accurate genetic relationship of several DNA sequence data. Kinship clearly and easily can be expressed in the form of a phylogenetic tree diagram (Phylogenetic Tree). This diagram represents kinship obtained from the elektroferogram process of electrophoresis sequencing of DNA bases. From some sequences experimental results using sequence analysis application program gradually, starting from installing, editing, and alignment so as to obtain the analysis and phylogenetic branching diagram view. This study uses a sequence analysis program Mega-7 (Molecular Evolutionary Genetics Analysis) to obtain a phylogenetic diagram for high accuracy and relatively easy to operate. This program can translate image data into nucleotide bases that shows the kinship of the distance the nearest branch with a standard sequence. The major advantage of this program is that it can do some analysis in a single program.